FAKTOR YANG MEMENGARUHI PERILAKU MASYARAKAT DALAM MEMBUANG SAMPAH SEMBARANGAN DI KELURAHAN RAPPANG - Ika Zaskia; Muhammad Ikbal; Lukman (Jurnal Publikasi Manajemen Informatika, 2025)
The purpose of this research is to identify the factors influencing the community’s behavior in littering in Rappang Village, Sidenreng Rappang Regency. The population in this study consists of all Heads of Families in Rappang Village, totaling 585 families. The sample in this study consisted of 86 respondents determined using the Slovin formula and random sampling technique. The type of research used is quantitative research. Data collection techniques were carried out through observation, questionnaires, and literature study. The data analysis technique was carried out with the help of the SPSS application. The research results show that the predisposing factors (knowledge, attitudes, and beliefs) have an average percentage of 83.8% and fall into the “very good” category. The enabling factors (facilities, infrastructure, and distance to polling stations) have a percentage of 59.3%, while the reinforcing factors (social support, environmental pressure, and policies) have a percentage of 60.8%, both of which fall into the “fairly good” category. Based on the results of the multiple linear regression analysis through the ANOVA test, an F value of 3.656 was obtained with a significance level of 0.016.Because this significance value is smaller than the 10% significance level (0.10), it can be concluded that this multiple linear regression model is significant simultaneously. The regression results show that the R square is 0.118, which means that approximately 11.8% of the variation in community behavior can be explained by predisposing factors, enabling factors, and reinforcing factors.